2022
DOI: 10.1002/jmv.27779
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationship between qAnti‐HBc and liver inflammation in chronic hepatitis B with normal or mildly elevated alanine transaminase based on liver biopsy

Abstract: The proportion of chronic hepatitis B (CHB) patients with normal or mildly elevated alanine transaminase (NMALT) levels who have moderate to severe inflammation was not rare. However, we lacked appropriate biomarkers to evaluate liver inflammation in these populations. We aimed to explore the relationship between quantitative hepatitis B core antibody (qAnti-HBc) and hepatic histological inflammation. This multicenter cohort study enrolled participants from 34 Chinese hospitals including 1376 treatment-naive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…Several studies have looked at the additional role of qAnti-HBc in identifying immune activation status and inflammation in HBV-positive persons with normal ALT levels[ 88 , 89 ]. Zhang et al [ 90 ] found that in 1376 untreated CHB patients with normal ALT, there was a dose-responsive association between the degree of liver inflammation and qAnti-HBc. The qAnti-HBc cut-off value for identifying moderate and severe inflammation was around 4.5 Log10 IU/mL.…”
Section: Qanti-hbcmentioning
confidence: 99%
“…Several studies have looked at the additional role of qAnti-HBc in identifying immune activation status and inflammation in HBV-positive persons with normal ALT levels[ 88 , 89 ]. Zhang et al [ 90 ] found that in 1376 untreated CHB patients with normal ALT, there was a dose-responsive association between the degree of liver inflammation and qAnti-HBc. The qAnti-HBc cut-off value for identifying moderate and severe inflammation was around 4.5 Log10 IU/mL.…”
Section: Qanti-hbcmentioning
confidence: 99%
“…There is mounting evidence that qAnti-HBc level not only correlates positively with the severity of liver inflammation but also decreases with the improvement of inflammation severity in patients receiving therapy [ 19 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. It was shown that serum qAnti-HBc level, ALT and liver inflammation activity were closely related [ 44 , 47 ].…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 99%
“…[ 21 , 37 , 39 , 40 ] (prediction of viral reactivation upon immunosuppression), refs. [ 19 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] (prediction of hepatic inflammation grade), refs. [ 50 , 51 , 52 , 53 ] (prediction of fibrosis stage), ref.…”
Section: Figurementioning
confidence: 99%
“…The commonly used marker for liver damage, ALT, carries a risk of missed detection, with 20–30% of patients with normal ALT experiencing moderate to severe liver inflammation. Extensive studies have investigated the additional role of qAnti-HBc in discriminating inflammation and immune activation status in individuals infected with HBV and with normal ALT levels [ 29 , 40 , 41 , 42 ]. In a multicenter study, Zhang et al revealed a dose-responsive relationship between qAnti-HBc and liver inflammation severity in 1376 untreated CHB patients with normal ALT (β = 0.48, p < 0.001), with the qAnti-HBc cut-off value for diagnosing moderate and severe inflammation at about 4.5 log10 IU/mL [ 41 ].…”
Section: The Qanti-hbc Levels In the Natural History Of Hbv Infectionmentioning
confidence: 99%
“…Extensive studies have investigated the additional role of qAnti-HBc in discriminating inflammation and immune activation status in individuals infected with HBV and with normal ALT levels [ 29 , 40 , 41 , 42 ]. In a multicenter study, Zhang et al revealed a dose-responsive relationship between qAnti-HBc and liver inflammation severity in 1376 untreated CHB patients with normal ALT (β = 0.48, p < 0.001), with the qAnti-HBc cut-off value for diagnosing moderate and severe inflammation at about 4.5 log10 IU/mL [ 41 ]. This study also noted that the decline of qAnti-HBc after NAs-treatment correlated with the alleviation of liver histological inflammation.…”
Section: The Qanti-hbc Levels In the Natural History Of Hbv Infectionmentioning
confidence: 99%